A STUDY ON SWING FROM VISIONS PROVIDED BY MEMBERS OF A VIRTUAL COMMUNITY OF LIBERAL SEXUAL BEHAVIOR - Gomez, Fernando [UNESP]; Marcal Ribeiro, Paulo Rennes [UNESP]; Custodio, Vagner Sergio [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This work aims to diagnose views on the sexuality of people with liberal sexual behaviors in the swingers' community and their opinions about motivation in the liberal sexual environment. For that, we have consulted a forum of a liberal sexual behavior website which has 16,589 registered profiles, being 13,640 couples, 2,276 men and 673 women, where members spontaneously discussed this issue. A total of 77 posts were classified according to the occurrence, analyzed, and commented on qualitatively. We seek to understand the rules for the exchange of couples, the question of pleasure in the swing, the concept of liberal sex and sexual fulfillment with this practice based on what the participants of the forum said, in the posts.
Keywords: Liberal sexual behavior; Sex; Swing; Web site